2018
DOI: 10.1016/j.smallrumres.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the levels of acute-phase protein and other serum protein fractions in Santa Inês ewes fed with a high-concentrate diet

Abstract: The aim of this study was to evaluate the effects of subacute ruminal acidosis (SARA) on total serum protein (TP), plasma fibrinogen (Fb), and serum protein fractions in seven hay-adapted Santa Inês ewes fed with a highconcentrate diet for 133 days. Blood was extracted, before feeding, by external jugular venipuncture into tubes with ethylenediaminetetraacetic acid dipotassium anticoagulant, to evaluate the Fb concentration by heat precipitation, and into plain tubes, for TP analysis by the Biuret method and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Besides, Li et al ( 2019 ) observed hepatic Hp upregulation in the newborn calves induced with subacute ruminal acidosis (SARA) through starch‐rich diet for 16 weeks, while Hp expression was not affected in adult dairy cows fed HC diet for 8 weeks (Guo et al, 2017 ). The upregulation of Hp is linked with ruminal acidosis, damaged GIT wall and elevated blood LPS levels thus the overexpression of Hp has been considered as potential marker of severe ruminal acidosis in ruminants (Girardi et al, 2018 ). Hence, lack of effect of HC diet on Hp expression suggests gradual adaptation to concentrated diet over a period (Chishti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Li et al ( 2019 ) observed hepatic Hp upregulation in the newborn calves induced with subacute ruminal acidosis (SARA) through starch‐rich diet for 16 weeks, while Hp expression was not affected in adult dairy cows fed HC diet for 8 weeks (Guo et al, 2017 ). The upregulation of Hp is linked with ruminal acidosis, damaged GIT wall and elevated blood LPS levels thus the overexpression of Hp has been considered as potential marker of severe ruminal acidosis in ruminants (Girardi et al, 2018 ). Hence, lack of effect of HC diet on Hp expression suggests gradual adaptation to concentrated diet over a period (Chishti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma AGP level initially decreased and then subsequently increased in sheep fed HC diet (Girardi et al, 2018 ) and the LPS challenge increased hepatic AGP expression in cow (Jiang et al, 2008 ). Though the role of AGP is not fully understood but several studies have shown its protective effects against inflammation and thus considered as powerful anti‐inflammatory agent (Brown et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation